DAMPAK PENILAIAN KINERJA APARATUR SIPIL NEGARA DALAM UPAYA PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA UNTUK PEMBANGUNAN BERKELANJUTAN - Bertha Lubis (GoAcademica Research dan Publishing, 2019)
In this study, one important thing will be discussed, namely about what is performance, its services, especially for the state civil apparatus (ASN). Since personnel are so important from both the employee and organizational point of view, an efficient evaluation orders related evaluations to the organization. The main objective of this research is to assess the importance of evaluating the performance of the civil service to increase public efficiency as a special type of human capital. This concludes with the steps necessary to ensure the efficient use of the capacity of the civil service of the state. This study uses a qualitative approach with a literature review method to explain the performance of the State Civil Apparatus as a development of the quality of human resources.